Byronizm jako transgresja (o Wielkiej Improwizacji w „Dziadach” części III Adama Mickiewicza) - Kalinowska, Maria (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
Based on the example of Byronic themes in Mickiewicz’s works from the 1830s, the author analyses the antinomies of Byronism’s receptions, focusing on the Great Improvisation as an archetypal scene within Polish romantic literature. Konrad’s improvisation expresses both the extreme solitude of the character and his deepest relationship with his community. The Great Improvisation is also a transgression in its multiple meanings. In this scene, we can see the peak of Polish Byronism as well as the end of Byronic influence. The dynamics of the Improvisation show that Mickiewicz’s Byronism cannot be treated solely in the categories of literary motifs, psychological construction or a set of ideas. In this case, Byronism is not merely a static collection of characteristics, but a dynamic construction, an activity full of tensions; it is a constant verification of ethical and religious values and ideals, if not a review of dogmas and traditions and the process of transgressing them in order not to arrive at nothingness and evil, but – as Mickiewicz put it – to “search for higher and fundamental truths.”